Protein C Level in Type 2 Diabetic Patients with Ischemic Heart Disease - State, Omnia Ibrahim; Hafez Ahmed, Hala Abdel; Abdel Shakour, Hany Mahmoud; Elaziz Farag, Nora Abd; Talaat Gaafar, Mohamed (Journal of Neonatal Surgery, 2025)
Background: Diabetes Mellitus is among the most important risk factors for the development of cardiovascular diseases. Macro vascular complications associated with diabetes, namely, coronary artery disease, cerebro vascular disease and peripheral vascular disease are mainly due to accelerated atherosclerosis. The aim of this work was to assess the relationship of the level of protein C in diabetic patients with ischemic heart disease versus normal individuals. Methods: case control study conducted on 90 with subjects who were classified into three equal groups: Group 1: diabetic patients without ischemic heart disease (normal coronary angiography). Group 2: diabetic patients with ischemic heart disease (with cardiac ischemia on coronary angiography). Group 3: Normal individuals as control. Results: The mean Protein C level was highest in the Control group followed by DM without IHD group and lowest in DM with IHD group. Protein C demonstrated good diagnostic performance in discriminating between diabetes groups. Protein C achieved an AUC of 0.731 and an accuracy of 78.3%. The optimal cut-off value of 64 provided a sensitivity of 93.33% and a specificity of 63.33%. Conclusions: Protein C levels were significantly lower in diabetic patients, especially those with ischemic heart disease (IHD), compared to healthy controls, linking Protein C deficiency to thrombotic complications. Multivariate analysis identified low Protein C levels and smoking as independent predictors of IHD severity. Protein C demonstrated strong diagnostic capability, indicating its potential as a useful biomarker for identifying vascular risk in diabetes..